Improvement of complex regional pain syndrome after plasmapheresis. (12th August 2014) - Blaes, F.; Dharmalingam, B.; Tschernatsch, M.; Feustel, A.; Fritz, T.; Kohr, D.; Singh, P.; Kaps, M.; Szalay, G.
Abstract: Complex regional pain syndrome is a severe complication following trauma that is associated with vasomotor, sudomotor and sensory disturbances in an affected limb or region of the body. The exact physiopathology is not fully understood yet. Recently, autoantibody findings suggested an immune‐mediated physiopathology of the disease. We here describe two otherwise treatment‐resistant patients with complex regional pain syndrome and high‐titre beta2 adrenergic receptor autoantibodies, who did respond to plasmapheresis. Both patients showed strong improvement of pain and autonomic symptoms measured by impairment level sum score.